2008
DOI: 10.1007/s10620-008-0437-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Turkish Children with Autoimmune Thyroiditis

Abstract: The close association between celiac disease (CD) and autoimmune disorders is well documented in adult and pediatric patients. The aim of this study is to determine the prevalence of CD in Turkish children with autoimmune thyroiditis (AT). Sera from 101 children with AT (11 boys and 90 girls, from 2 to 18 years of age; mean age 12.28 +/- 3.26 years) and 103 healthy children (46 boys and 57 girls, from 3.5 to 17 years of age; mean age 12.18 +/- 3.11 years) were screened for CD using the IgA anti-tissue transglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…In a study conducted by Sattar et al (32) in children, dTG-IgA was found to be positive in 14 (4.6%) of 302 subjects with autoimmune thyroiditis and it was reported that the diagnosis of CD was confirmed with intestinal biopsy in seven of these subjects (2.3%). In our country, it was reported that five subjects (4.9%) were diagnosed with CD in a study conducted by Sarı et al (31) with children and adolescents with a diagnosis of autoimmune thyroditis. In a study conducted with healthy school age children in Turkey, the frequency of CD was reported to be 1:212 (0.47%) (33).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a study conducted by Sattar et al (32) in children, dTG-IgA was found to be positive in 14 (4.6%) of 302 subjects with autoimmune thyroiditis and it was reported that the diagnosis of CD was confirmed with intestinal biopsy in seven of these subjects (2.3%). In our country, it was reported that five subjects (4.9%) were diagnosed with CD in a study conducted by Sarı et al (31) with children and adolescents with a diagnosis of autoimmune thyroditis. In a study conducted with healthy school age children in Turkey, the frequency of CD was reported to be 1:212 (0.47%) (33).…”
Section: Discussionmentioning
confidence: 89%
“…In studies conducted with adults, the prevalence of CD has been reported to be 10.8-3.3% in subjects with autoimmune thyroid disease (28)(29)(30). In studies conducted with children, the prevalence of CD has been reported to be 0.3-1.2% in healthy children and 1,3-6,5% in children and adolescents with a diagnosis of autoimmune thyroiditis (31,32). In a study conducted by Sattar et al (32) in children, dTG-IgA was found to be positive in 14 (4.6%) of 302 subjects with autoimmune thyroiditis and it was reported that the diagnosis of CD was confirmed with intestinal biopsy in seven of these subjects (2.3%).…”
Section: Discussionmentioning
confidence: 99%
“…22 Currently, the best approach is to focus on case findings by screening individuals who are known to have a higher risk of celiac disease. 20 The commercially available diagnostic tests for celiac disease are antigliadin antibody (AGA), EMA and TTG. In comparison with the other tests, AGA presents lower specificity (< 90%), and hence its use is no longer recommended in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria for autoimmune thyroiditis comprised positivity for antithyroglobulin (ATG) and antithyroid peroxidase (ATPO) antibodies and altered serum thyroid stimulating hormone (TSH) or a positive ultrasound examination. 19,20 Clinical, laboratory and histological findings were collected from the data contained in the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…αντιπροσωπεύουν το υποκλινικό φάσμα συγκεκριμένων αυτοάνοσων νόσων ή απλά αντανακλούν μια επίδραση της ηλικίας στο σύστημα αυτοανοσοποίησης. Η κοιλιοκάκη είναι μια αυτοάνοση νοσολογική οντότητα , της οποίας η έναρξη πυροδοτείται από τη γλουτένη ωστόσο η πλειονότητα των μελετών μέχρι σήμερα χρησιμοποιεί δεδομένα νεαρών ηλικιακών ομάδων και τα αντίστοιχα όρια τιμών για τη διάκριση της οροθετικοτητας με βάση τα αντισώματα έναντι της τρανσγλουταμινάσης προέρχονται από τις ομάδες αυτές [115][116][117]. Ωστόσο φαίνεται πως υπάρχει μια αύξηση των παραγομένων αντισωμάτων με την πρόοδο της ηλικίας.…”
Section: στοματικά έλκη άφθες και κοιλιοκάκηunclassified